A method for barrier‐based incident investigation. Issue 4 (27th June 2015) - Pitblado, Robin; Potts, Tony; Fisher, Mark; Greenfield, Stuart
Abstract : Incident investigation is a formal requirement for high hazard facilities with the aim to learn from each incident and to prevent future recurrences. There are many published investigation methods, with most driving to the management system root cause and some applying newer barrier‐based methods. However, these methods either do not link tightly to the facility risk assessment or are very difficult to apply, and lessons from incidents that might reveal weaknesses, especially relating to major accidents, can be missed. This article describes a novel method for incident investigation (Barrier‐based Systematic Cause Analysis Technique) that combines the ideas of barrier‐based risk assessment with a well‐established systems‐based root cause analysis method (Systematic Cause Analysis Technique). The method described is efficient and can be applied by properly trained supervisors, and this potentially allows every incident or near‐miss event to be assessed in a consistent risk‐based format. The method clearly establishes links back to the facility risk assessment and thus identifies risk pathways that are potentially too optimistic (i.e., the risk is higher than predicted), and this can be due to initial optimism or degradation of safety barriers (human or hardware). © 2015 American Institute of Chemical Engineers Process Saf Prog 34: 328–334, 2015